Effect of ethanol on the performance, emission and combustion characteristics of a compression ignition engine fuelled with vegetable oil–diesel blend. Issue 3 (3rd May 2016) - Qi, D.H.; Lee, C.F.; Wang, P.P.; Wu, S.T.
Abstract : Experimental work had been carried out to analyse the effect of ethanol on the performance, emission and combustion characteristic of vegetable oil–diesel blend (50% vol. rapeseed oil and 50% vol. diesel fuel). The vegetable oil–diesel–ethanol blended fuels were prepared by using microemulsification technique and the main properties were measured. The results showed that, with the increase in ethanol volume fraction in the blends, the viscosity and density were decreased and close to those of diesel fuel. The combustion started later; the peak cylinder pressure, peak heat release rate varied significantly under different operating conditions and the corresponding crank angles of the peak values were retarded. There were slightly higher brake-specific fuel consumptions. Smoke and nitrogen oxide emissions were observed to reduce, but carbon monoxide and hydrocarbon emissions were found slightly higher with the increase of ethanol volume fraction under all ranges of engine operating conditions.